The impact of a practical treatment program in enabling victims of bullying in a sample of 6th graders (Journal of the College of Education for Women, 2019)
This study was aimed to explore the impact of a practical program on supporting and reducingsymptoms of school bulling victims in a sample of student in the sixth grade. The study sample consisted of (18)students that have been chosen from two schools (Al-Abass and Alataa’) it was an intended sample, becausethere were enough student with high scores in bulling victims diagnostics test, the sample was divided into twogroups: the control group of (9) student from (Alataa’) school, and the experimental group consisted of (9)student from Alabass) school keeping in mind to keep the two groups equivalent in maintaining equal controls.The researcher applied the practical program which is based on cognitive behavioral therapy with theindividuals of the experimental group. The program consisted of 13 sessions, 50 minutes each. The control group did not receive any treatment. To achieve the purpose of the study, school bulling diagnosis have been applied to chose the sample of the study, a scale was also used on bulling victims to know the intensity or level of bulling the victims have been exposed to. Data was analyzed statistically based on tests of (Wilcoxon) and (Mann Witney) to measure the effect of the treatment in school bulling victims. Results show significant differences between the two tests pre and after in favor of the experiment group after applying the program, the other hand there wasn’t any differences in the pre and after test in the control group.